Barriers and Strategies for Implementing Occupational Health and Safety (OHS) for Women Workers in the Pasuruan Textile Industry - Lutfia Wirdatul Ajizah; Sukesi , Keppi; Endrawati , Lucky (Graduate School Universitas Brawijaya, 2026)
Objective: This study analyzes the barriers and strategies for implementing Occupational Health and Safety (OHS) for women workers in the textile industry, emphasizing how a gender perspective shapes their experiences and bargaining power in OHS practice. Design/Methods/Approach: using a qualitative-descriptive design grounded in Participatory Action Research (PAR), data were collected through structured observation and in-depth interviews at CV. Semoga Jaya, Pasuruan, involving seven women workers (tying and drying divisions) and one management informant (purposive sampling). Findings: Four problem nodes emerged: (i) personal protective (PPE) is available but not mandatory and is often ignored; (ii) written standard operating procedures (SOPs) are absent and machinery maintenance is reactive; (iii) the physical work environment is polarized (overheated, poorly ventilated enclosed areas versus semi-open areas); and (iv) gender-sensitive facilities are limited (no private resting space/lactation room). In response, workers rely on horizontal solidarity and individual initiative as coping strategies, which paradoxically plug systemic gaps without addressing institutional root causes. Originality/Value: Theoretically, the research underscores the value of a gender-responsive, holistic OHS framework to assess not only hazards but also institutional capacity and equitable access to protection. Practical/Policy implication: The study proposes a sequenced intervention package: enforcement of PPE compliance and rapid socialization (?3 months), alongside the establishment of SOPs, a preventive maintenance program, and the provision of gender-responsive facilities as structural improvements (?6 months); practically, it offers a realistic and measurable implementation roadmap.. Keywords: adaptive strategies; gender perspective; OHS; textile industry, women works JEL Classification: J28; J16; J81